Analysis of Social Work with Families in the Chilean Child Protection System: Difficulties and Challenges for the Consolidation of the Clinical Approach. - de-Toro Consuagra, Ximena; Sharim Kovalskys, Dariela; Fombuena Valero, Josefa (Clinical Social Work Journal, 2025)
One of the fields of social work where the clinical approach is highly relevant is family intervention. In the case of Chile, such intervention mainly occurs in programs for prevention, repair, and protection of children and their families. However, while family support programs have been extensively studied in Anglo-Saxon countries, yielding valuable information that has allowed for the adaptation of intervention models and the improvement of services provided, studies in this area and linked to the protection system are scarce in Chile. This qualitative longitudinal research aims to analyze the practice with families carried out by social workers to assess the extent to which the clinical approach is deployed within such practice and what would be required to advance in greater legitimacy. For eleven months, six dyads formed by a social worker and a family caregiver were followed. Data were collected both at the documentary level, with an in-depth analysis of the reports issued to courts, and at the level of empirical collection through observation, in-depth interviews, discussion groups, and session-to-session interviews. Finally, a thematic analysis was conducted. The results show that the clinical approach of social work in Chile is present in practice, but further training is required to advance its consolidation and legitimacy. It is observed that interventions that reach a higher level of reflexivity are those that would facilitate greater subjective change than those of an exclusively socio-educational nature. This could impact the relevance of Clinical Social Work in the field of child protection. Then, challenges for training and the relevance of a relational-collaborative, contextual-anti-oppressive, and feminist perspective are discussed to facilitate new paths of transformation where families are considered experts in their own lives.